Playing God Belief and Ritual in the Muttappan Cult of North Malabar. - Gabriel, Theodore (London : Equinox Pub., 2010)
Playing God analyses the mythology and ritual praxis of the Muttappan cult and examines attempts to integrate the cult into a wider Hinduism by enunciating a new hermeneutic of the legend and rituals based on the Hindu Advaitic tradition. The book also discussed how the Teyyam ritual contrasts significantly with rituals and worship in Brahminical Hinduism.
Cover; Contents; Acknowledgements; Foreword; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Notes; Bibliography; Books in English; Journal articles (in English); Books in Malayalam; Index.
Description based on print version record.
Keywords: Hinduism -- India -- Malabar Region -- Rituals; Muttappan (Hindu deity) -- Cult -- India -- Malabar Region; Theyyam (Dance) -- Social aspects -- India -- Malabar Region; Muttappan (Hindu deity) -- Cult -- India -- Malabar Region; Hinduism -- India -- Malabar Region -- Rituals; Theyyam (Dance) -- Social aspects -- India -- Malabar Region; RELIGION / Hinduism / Rituals & Practice; Electronic books